Revisiting Offsets of Psychotherapy Coverage - Benjamin Ly Serena (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
Mental illness is a leading cause of disability worldwide with vast costs to society. Yet, insurance coverage for effective treatments remains limited. This paper revisits the Offset Hypothesis, which claims insurance coverage for psychotherapy is self-financing through reductions in the use of other health care services and improved labor market outcomes. I study a 2008 reform of the Danish public health care system that introduced 60 percent coverage of the cost of psychotherapy for depression and anxiety patients below age 38. Using Regression Discontinuity and Difference-in-Difference designs, I show that psychotherapy coverage reduces the use of other mental health services, physical health care and suicide attempts, but does not impact employment, sick leave or disability pension receipt. Still, the reduction in health care costs is sufficiently large to finance the policy. This suggests mental health coverage is both welfare improving and cost reducing.
Keywords: I13; I18; I38; H51; H55; 330; mental health; health insurance; health care; offset; labor market